Potensi Serapan Karbon Hutan Mangrove Pesisir Sinjai Utara Kabupaten Sinjai: Carbon Absorption Potential Of Mangrove Forests North Sinjai Coast, Sinjai District - Azizah, Rahmah; Alamsyah, Ridha; Mutahharah, Mutahharah; Akram, Akram; Nurhaliza, Nurhaliza; Maulana, Wahyu (HUTAN TROPIKA, 2024)
Mangroves play an important role in carbon storage and absorption. Mangrove ecosystems absorb carbon dioxide from the atmosphere through photosynthesis, converting it into biomass. Mangroves can store up to four times more carbon per unit area than tropical forests. This study aims to determine the density, stem diameter, basal area of ​​mangroves, biomass, content, and the ability of mangroves to absorb carbon in the air. The method used is the calculation of several ecological indices. While the carbon content and absorption use the allometric method to determine the biomass of mangrove species. Furthermore, the calculation of carbon content and carbon absorption capacity. The average density of mangroves obtained ranges from 0.24-0.55 ind / m2, while the average DBH is between 6.86-16.10 cm and the average basal area is 36.94-203.48 m2. The average biomass of mangrove trees is 13,311-98,752 kg / tree or 288,885 ± 96,957 tons / ha. The average carbon content is6,256-46,414 kg/tree or 107,576±45,570 tons/ha. The carbon absorption capacity of the coastal mangrove forests of North Sinjai is an average of 22,961-170,338 kg/tree or 394,803±167,241 tons/ha. Mangroves are one of the key components in climate change mitigation. Conservation and restoration of mangrove ecosystems are important strategies in efforts to mitigate global climate change and improve the sustainability of coastal environmental ecosystems.